Telehealth Finance Variables and Successful Business Models - Arkwright, Bryan T.; Leslie, Monica; Light, Morgan (Telehealth and Medicine Today, 2019)
Successful telehealth business models are a topic of regular discussion in the healthcare industry, and the financial details of telehealth programs, initiatives, and companies are central to program viability and sustainability. Claims and total payments toward telehealth services are rapidly increasing each year; therefore, it is becoming imperative that organizations carefully navigate the regulatory, financial, operational, and technical aspects impacting, and many times determining, the financial health of telehealth programs. The objective of this article is to define and articulate the financial variables and business models that are the lifeblood of today’s successful telehealth programs, and also to provide insights and information to assist organizations in navigating the nuances of telehealth financial modeling, monitoring, and management. The financial and business models surrounding telehealth are unique for a number of reasons, mainly because the calculations and architecture of such models often contain many continuous variables, such as people (clinical providers and patients), geography (rural or metropolitan areas), telehealth governance structure, the service provided, the reimbursement or coverage eligibility, the technology used, the quality of care rendered, and the outcome of the care rendered. In addition, a clear need for a departure from traditional ways of projecting return on investment (ROI) becomes apparent with the layering of additional complexities of restrictive payer requirements, various business models, and the transition from volume to value.